IDENTIFIKASI DAN OTENTIFIKASI CITRA WAJAH MENGGUNAKAN JARINGAN SARAF TIRUAN SOM DAN KONVOLUSI - Mulyani, Yessy
ABSTRACT: Faces represent complex, multidimensional, meaningful visual stimuli and developing a computational model for face recognition is difficult. This thesis learn how to have the solution of face identification and face authentification with neural network approach. The Self Organizing Map neural network and the Convolutional Neural network use in this solution. The Self Organizing Map provides a quantization of the images samples into a topological space where inputs that are nearby in the original space are also nearby in the outputs space, thereby providing dimensionality reduction and invariance to minor changes in the sample images, and the convolutional neural network provides for partial invariance to translation, rotation, scale, and deformation. The convolutional network extracts successively larger features in a hierarchical set of layers with the backpropagation algorithm. For best parameter, this system can do face identification and authentification in 76% and 75% measure of confidence respectively.